Resin‐coated urea effectively simulates the chronic dynamics of natural nitrogen deposition - Yi Zhao; Yuguang Ke; Honghui Wu; Chong Xu; Xiwen Li; Yann Hautier; Elizabeth T. Borer; Qiang Yu (Methods in Ecology and Evolution)
Abstract Atmospheric nitrogen (N) deposition has more than tripled globally since the Industrial Revolution. Experiments usually simulate N deposition using fast‐release N fertilizers applied once or several times a year. However, these pulses differ from the continuous N supply of natural deposition, which may lead to different outcomes. There is an urgent need for methodologies that more accurately replicate continuous N deposition to better understand its causal impacts on future biological outcomes. We developed a resin‐coated slow‐release urea to stimulate the continuous N deposition dynamics in semiarid grasslands. Three urea ball sizes with varying resin coating thicknesses were designed to achieve year‐long release. We then compared the N release rate of the coated fertilizer to rate of natural N deposition to assess its effectiveness in replicating the temporal pattern of N deposition. Our results showed that under the semiarid conditions of our site, the resin‐coated urea with a 0.5 mm coating on 4 mm diameter balls released urea continuously for approximately 12 months. The temporal pattern of N release rate of the fertilizer was very similar to local atmospheric N deposition. There was a strong positive relationship between N release rates and N deposition (R2 = 0.80), with both exhibiting simultaneous peaks and valleys. Our results indicate that resin‐coated urea with a pellet size and coating thickness determined by local site conditions can effectively simulate the temporal dynamics of N deposition. Coated urea provides a far more effective approach for experimentally simulating future impacts of elevated N deposition on ecosystem function and processes compared to fast‐release fertilizers.